Social media impact on qualitative performance metrics: Analysis and trends of top revenue grossing U.S. Hospitals. Issue 3 (3rd July 2022) - Sakulsaengprapha, Vorada; Masterson, Jonathan P.; He, Waverley; Schilling, Andrew; Shi, Galen; Mathews, Simon C.
Abstract: Social media is a common, multi-purpose tool used by most hospitals to engage a broad audience. The relationship between hospital social media activity and performance on influential reputation and patient experience ratings is not well described. The aim of this study was to characterize social media activity across the top 100 revenue grossing U.S. hospitals and its impact on key patient experience and hospital rankings. While nearly all top 100 revenue grossing U.S. hospitals have a presence on social media, usage and following significantly varied. Social media activity metrics collected showed some limited association with reputation and patient experience-influenced rankings.